A cyclosporine derivative is a substrate of the oligopeptide transporter PepT112. Issue 5 (29th March 2016) - Foley, David W.; Bermudez, Isabel; Bailey, Patrick D.; Meredith, David
Abstract : Cyclosporine was attached to a thiodipeptide carrier, yielding conjugate7 ; this is a substrate for PepT1 with oral bioavailability potential. Abstract : The mammalian proton-coupled oligopeptide transporter PepT1 is recognised as an important route of oral drug delivery. Peptide-based compounds offer great potential as drugs but their application is limited by poor membrane permeability, amongst other challenges. Using cyclosporin A as a proof-of-concept, we demonstrate for the first time that peptidic molecules over 1000 Da in size can be targeted towards and transported by PepT1.